WATER EROSION UNDER THREE TILLAGE METHODS IN A CULTIVATION OF Eucalyptus benthamii - Padilha, Juscélia; Bertol, Ildegardis; Magro, Bruno Afonso; Bagio, Bárbara; Marioti, Juliana; Ramos, Júlio César (Revista árvore, 2017)
ABSTRACT Soil tillage influences the development of forests planted in the initial phase, which affects some hydrological processes and water erosion. The objective of this study was to quantify the water losses (WL) and soil losses (SL) by water erosion, between the second and third years of eucalyptus (Eucalyptus benthamii) crop, in an experiment located in southern Brazil, on a Humic Dystrudept. Was study three soil tillage treatments: i) subsoiling in downslope direction (SD); ii) subsoiling in contour on the slope (SC); iii) manual holes (MH). The plots had a dimension of 12 x 24 m, being the slope-wise length the greatest, monitored by tanks placed at the lower end for runoff collection. Runoff volume measurement and sampling for subsequent calculation of WL and SL was carried out weekly, corresponding to the rains accumulated during the week. The crop of eucalyptus in SD treatment, weakened the soil as to the water erosion in relation to the crop made in SC and in MH; the difference was 25% for the WL and 53% for the SL. Eucalyptus reforestation played an important role in the control of water erosion, regardless of the type of soil tillage. The SL due to water erosion were more influenced than the WL, regardless of the type of soil crop used. WL and SL are related to each other and to rainfall height in positive linear relationship, regardless of the type of soil preparation used for eucalyptus planting. RESUMO O preparo mecânico do solo é uma das operações mais importantes de manejo na fase inicial de desenvolvimento das florestas plantadas, pois afeta alguns processos do ciclo hidrológico e a erosão hídrica, sendo, por isso, importante o conhecimento dessas variáveis. Com o presente trabalho objetivou-se quantificar as perdas de água e solo por erosão hídrica pluvial, entre o segundo e o terceiro ano de cultivo do Eucalyptus benthamii, em um experimento situado no Sul do Brasil, sobre um Cambissolo Húmico alumínico léptico, em três tratamentos de preparo do solo: i) preparo com subsolagem a favor do declive; ii) preparo com subsolagem em contorno ao declive; iii) preparo em covas com coveador manual. As parcelas tinham dimensão de 12 x 24 m, com o maior comprimento no sentido do declive, monitoradas por tanques colocados ao seu final para coleta da enxurrada. A medição do volume e a coleta de amostras da enxurrada para posterior cálculo de perdas de água e solo foi realizada semanalmente, correspondendo às chuvas acumuladas na semana. O preparo do solo a favor do declive apresentou perdas de água e solo maiores do que em contorno e em covas, cuja diferença foi 25 % para as perdas de água e 53 % para as perdas de solo. O crescimento das plantas ocasionou sensível diminuição do escoamento superficial, evidenciando que o reflorestamento, nas condições experimentais, pode controlar a erosão hídrica. As perdas de solo por erosão hídrica foram influenciadas em magnitude maior do que as perdas de água, independentemente do sistema de preparo do solo e da forma de plantio de Eucaliptus benthamii.